Molecular Order in Buried Layers of TbPc2 Single‐Molecule Magnets Detected by Torque Magnetometry. Issue 32 (27th May 2016) - Perfetti, Mauro; Serri, Michele; Poggini, Lorenzo; Mannini, Matteo; Rovai, Donella; Sainctavit, Philippe; Heutz, Sandrine; Sessoli, Roberta
Abstract : Cantilever torque magnetometry is used to elucidate the orientation of magnetic molecules in thin films. The technique allows depth‐resolved investigations by intercalating a layer of anisotropic magnetic molecules in a film of its isotropic analogues. The proof‐of‐concept is here demonstrated with the single‐molecule magnet TbPc2 evidencing also an exceptional long‐range templating effect on substrates coated by the organic molecule perylene‐3, 4, 9, 10‐tetracarboxylic dianhydride.